Innovative Leadership Practices and Management Styles of School Heads in the Schools Division of Bulacan - Hernandez, Mhelbie M.; Mendoza, Sherlaine D. C.; Pacheco, Marichrin M. (Future Science / FSH-PH Publications, 2023)
The study aimed to describe and examine school heads’ innovative leadership practices and management styles among school heads assigned in Bustos District in the Schools Division of Bulacan. The study was participated by thirteen (13) school heads who were purposively drawn by the researchers. Results revealed that school heads always practiced innovative leadership practices in terms of strategic thinking, innovative thinking, action patterns and interpersonal skills. Hence, school heads always practiced sound management styles which enabled them to create sound and efficient managerial and supervisory functions. Further, strategic thinking is negatively correlated with instructional leadership as implemented by the school heads.